Interlaminar fracture toughness of a plain weave flax/epoxy composite. (7th February 2019) - Rajendran, T.S.; Johar, M.; Low, K.O.; Abu Hassan, S.; Wong, K.J.
ABSTRACT: In recent decades, flax fibre has become a popular natural resource as reinforcement in polymeric composites. However, the pure mode characterisation of flax fibre composites is rather limited. Furthermore, the mixed-mode delamination is not yet available. Nevertheless, delamination behaviour is important to be characterised as it is a major problem in composite laminates. This study examined the delamination behaviour of a woven flax/epoxy composite. Specimens were tested using mode I double cantilever beam, mode II end-notched flexure and mixed-mode I+II single leg bending tests. Results showed that the mode I, mode II and mixed-mode I+II fracture toughness were 363.23, 962.17 and 649.06 N m −1, respectively. When the fracture toughness values were fitted using Benzeggagh–Kenane criterion, it was found that the best-fit material parameter η was attained at 0.88. This information is useful to estimate the variation of fracture toughness with the mode ratio. Finally, through scanning electron micrographs, it was noticed that fibre/matrix debonding was the major fracture mechanism in all loading modes. In conclusion, the findings from this study suggested that the composite was suitable to be used for structural applications under mixed-mode loading.